Exploring Mate Selection Preferences in Indonesia: A Preliminary Study for Instrument Development in Non-formal Education Contexts - Mira Ariyani; Lussy Dwiutami Wahyuni; Fildzah Rudyah Putri; Kurniati Kurniati; Musab Isah (Universitas Negeri Semarang, 2025)
Background: Mate selection preferences is an evaluation process that aims to find a partner who is considered potential for someone. This study was inspired by Buss and Barnes' study regarding mate selection preferences, as well as Hinkin, Tracey, and Enz's study regarding the seven stages of scale development and analysis; to investigate Indonesians’ mate selection preferences. Research objectives: This study was considered as a replication research for Indonesia context to verify the prior results’ consistency and accuracy of research on mate selection preferences inspired by Buss and Barnes as well as to develop an instrument of mate selection preferences for Indonesians. Research methods: This study used three stages –out of seven stages– of scale development and analysis by Hinkin, Tracey, and Enz as an early investigation. The first stage is item generation using a qualitative approach with a total of 47 participants aged over 17 years were divided into four focus groups as data collection method and thematic analysis as its analysis method. The second stage is content adequacy assessment using quantitative approach with eleven experts to assess generated items from the first stage. The eleven experts consisted of measurement experts, psychometricians, psychologists, developmental and family psychology lecturers or scientists. The third stage is questionnaire administration for determining the scale for items and an adequate sample size. The questionnaires using rank order scale were distributed online for 423 respondents. Research findings: The finding of the first stage was 33 themes of mate selection preferences, including same religion, ethnicity consideration, family blessing, attractive physical appearance, mentally and physically healthy, as item generation. The result from the second stage was the validation from experts, resulted in 22 characteristics with a validation range of 0.345 – 0.831 and a good category of reliability of 0.898. The result from the third stage was the order of preference for choosing a partner, was obtained by placing the characteristic of same religion as the first order. Research conclusions: The results of the first three stages in this research can be used as a starting point to understand how Indonesians select partners who are influenced by characteristics of same religion, cultural or ethnicity considerations, and family blessing. The same religion was ranked first in the order of mate selection preferences. This study then should be continued to the next four stages of instrument development in order to create a final scale of Indonesians’ mate selection preferences. Research novelty: The unveiling of Indonesians mate selection preferences as an early investigation introduces the “richness” and the wisdom of Indonesian cultures in marriage as well as appreciation and understanding of how marriages in Indonesia are bound by religions, cultures or ethnicity, and family values. It also informs the complexity of how to find an ideal partner. However, this study is practically can be used to non-formally educate Indonesian people as well as foreigners to understand how Indonesians select partners.